(untitled) (Physical Education, Health and Social Sciences, 2026)
Nurse burnout and job dissatisfaction in tertiary care hospitals represent a systemic crisis, exacerbated by high demands such as workload, emotional labor, and work-life interference, leading to exhaustion, depersonalization, reduced personal accomplishment, and turnover rates up to 30–50%. Drawing on the Job Demands-Resources (JD-R) model and Conservation of Resources (COR) theory, this review examines how job demands initiate health impairment processes, while resources like supervisor support and autonomy foster motivation and resilience. Global prevalence data indicate burnout affects 20–80% of nurses, with tertiary settings showing higher rates due to patient acuity and shift work. Assessment tools, including the Maslach Burnout Inventory (MBI) and Minnesota Satisfaction Questionnaire (MSQ), reveal correlations between burnout and dissatisfaction, impacting patient safety and healthcare costs (estimated at 4.6 billion annually in the US). Interventions such as mindfulness-based stress reduction (MBSR), social-emotional learning (SEL) programs, and organizational reforms (e.g., flexible scheduling) demonstrate 15–40% reductions in burnout symptoms. In resource-constrained regions, targeted strategies are essential to enhance retention and well-being amid ongoing shortages.